Pengaruh Struktur Modal, Inflasi, Dan Perputaran Modal Kerja Terhadap Harga Saham - Rahayu, Novianti Dwi; Lindawati, Lindawati (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze the effect of capital structure, inflation and working capital turnover on stock prices in companies indexed by Kompas 100 and listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. Sampling in this study used purposive sampling method and obtained 29 companies as samples. The data used in this study are secondary data obtained from www.idx.co.id and from the Bank Indonesia website, www.bi.go.id. The data analysis method used is quantitative data using panel data regression analysis using E-views 12. The results of this study indicate that capital structure, inflation, and working capital turnover simultaneously affect stock prices. However, partially, capital structure and working capital turnover have no effect on stock prices, while inflation partially affects stock prices.